HUMANICAL VALUES AND ENVIROMENTAL VALUES IN THE FOLKLORE AT THE REGION KARANGJATI DISTRICT, NGAWI REGENCY: LITERARY ECOCRITIC APPROACH - Claudia, Vinsca Sabrina; Suwandi, Sarwiji; Wardani, Nugraheni Eko (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The folklore found in Ngawi regency is very diverse, scattered in various districts. Circumstances like this give the origin of the name of the area can be created through the conditions of the environment. Furthermore, providing values and symbols through Natural Resources as the unifier and strengthening of society. This makes the folklore of the origins of the village in Karangjati district, Ngawi regency as an expression of oral literature with a dimension of concern for humans and nature. So, the problem of concern is related to the value of human care for humans or humans with nature and even nature with humans. The main problem in this research is about how humanist values and environmental care values are contained therein. This research has the aim of describing and explaining the various humanist values and environmental care values of the folklore stories of village origins in Karangjati district. The type of approach used is the ecocritical approach that focuses on the literary field. This study uses a qualitative descriptive method by taking data in the form of content analysis. The results showed that there were four folklore in Karangjati district with ecological nuances, namely (1) The Origin of Sembung Village; (2) The Origin of Karangmondo Hamlet, Rejomulyo Village; (3) The Origin of Sumberan Hamlet, Rejomulyo Village, and (4) The Origin of Sawo Village. Meanwhile, in terms of humanist values, there is a lot of data found in the stories of the origins of Sembung and Rejomulyo villages. On the other hand, the two values can provide an early teaching especially the younger generation about the importance of ecology in the community.